Measuring the Concentrations of Asbestos Fibers in Some Crowded Areas of Baghdad in The Summer of 2020 - Nahla Sh. Ajeel, Nada A. Fleeh, Matham A. Sultan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims of this research to determine asbestos fibers levels in surrounding air of some crowded sites of Baghdad city were monitored in summer 2020. Collection of samples was conducted by directing air flow to a mixed cellulose ester membrane filter mounted on an open‑faced filter holder using sniffer a low flow sampling pump, samples of air were collected from five studied areas selected in some heavy traffic areas of Baghdad city, (Al-Bayaa and Al-Shurta tunnel, Al-Jadriya, and Al-Meshin commercial complex, control), then analyzed to determine concentrations of asbestos fibers. Counting of asbestos on the filters was carried out through using both scanning electron microscope SEM and an energy dispersive X‑ray system EDS to count and determine asbestos fibers. The results of this research appeared that the levels of asbestos fibers which recorded minimum value in control site was 0.018±0.001 f/ml and maximum value in Al-Gadriya was 0.121±0.006 f/ml. The concentrations of asbestos fibers in all studied areas were more than standards of world health organization WHO for air was 0.0022 f/ml. This may be because the presence of crowded traffic, occurrence of industries near studied areas. Therefore, effective plans like management of traffic, changing of industrial locations, and products substitution replacement can be effective in reduce concentrations of asbestos fibers. Keywords: Asbestos Fibers, SEM, Crowded Areas, Ambient Air, Summer.